2020
DOI: 10.1038/s41550-019-1008-4
|View full text |Cite
|
Sign up to set email alerts
|

The LISA–Taiji network

Abstract: Both LISA and Taiji, planned space-based gravitational-wave detectors in orbit around the Sun, are expected to launch in 2030-2035. Assuming a one-year overlap, we explore a potential LISA-Taiji network to fast and accurately localize the gravitational-wave sources.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 145 publications
(103 citation statements)
references
References 13 publications
0
102
0
1
Order By: Relevance
“…During the same period, Chinese space-based GW detectors Taiji [11][12][13] [proposed by the Chinese Academy of Sciences (CAS)] and TianQin [17][18][19] (proposed by the Sun Yat-Sen University (SYSU)) will be launched. The synergic operation of these GW networks would contribute greatly on cosmology and the test of GR [528,559,[561][562][563][564][565][566].…”
Section: -15mentioning
confidence: 99%
See 2 more Smart Citations
“…During the same period, Chinese space-based GW detectors Taiji [11][12][13] [proposed by the Chinese Academy of Sciences (CAS)] and TianQin [17][18][19] (proposed by the Sun Yat-Sen University (SYSU)) will be launched. The synergic operation of these GW networks would contribute greatly on cosmology and the test of GR [528,559,[561][562][563][564][565][566].…”
Section: -15mentioning
confidence: 99%
“…• Moreover, the space-based GW observatories, such as LISA, Taiji, and TianQin, could form a space-based GW detection network in the future [562]. In ref.…”
Section: Standard Sirens Combined With Other Cosmological Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to LISA, Taiji is slightly more sensitive to low-frequency GWs due to its longer arms [ 2 ]. Since Taiji would launch in the same period [ 3 ], it is possible to combine these two space-based GW observatories into a LISA-Taiji network [ 4 ], which can improve the sky localization of GW sources due to the faraway separation of the two constellations ( Figure 1 ). In this letter, we investigate for the first time the network's potential ability to localize GW sources (Notice that the localization capacity of the LISA-Taiji network was further studied in [ 5 ] after the present work appeared on arXiv.).…”
Section: Introductionmentioning
confidence: 99%
“…Ruan et al [4] proposed for the first time the conception of the LISA-Taiji network for greatly improving the detection capability, and found that once LISA and Taiji form a detector network, the location precision of GW sources could be improved by almost four orders of magnitude [4][5][6]. This helps identify the host galaxies of MBHBs and increase the detection rate of EM counterparts, thus greatly optimizing the detections of standard sirens compared to the single GW observatory.…”
mentioning
confidence: 99%